Management guidelines for pregnant health care workers exposed to infectious dermatoses - Vidhatha Reddy, BA; Alexander L. Kollhoff, BS; Jenny E. Murase, MD; Kathryn Martires, MD (Wolters Kluwer, 2020)
Exanthematous diseases are frequently of infectious origin, posing risks, especially for pregnant health care workers (HCWs) who treat them. The shift from cell-mediated (Th1 cytokine profile) to humoral (Th2 cytokine profile) immunity during pregnancy can influence the mother's susceptibility to infection and lead to complications for both mother and fetus. The potential for vertical transmission must be considered when evaluating the risks for pregnant HCWs treating infected patients because fetal infection can often have devastating consequences. Given the high proportion of women of childbearing age among HCWs, the pregnancy-related risks of exposure to infectious diseases are an important topic in both patient care and occupational health. Contagious patients with cutaneous manifestations often present to dermatology or pediatric clinics, where female providers are particularly prevalent; a growing number of these physicians are female. Unfortunately, the risks of infection for pregnant HCWs are not well defined. To our knowledge, there is limited guidance on safe practices for pregnant HCWs who encounter infectious dermatologic diseases. In this article, we review several infectious exanthems, their transmissibility to pregnant women, the likelihood of vertical transmission, and the potential consequences of infection for the mother and fetus. Additionally, we discuss recommendations with respect to avoidance, contact, and respiratory precautions, as well as the need for treatment after exposure.